PENGELOLAAN DANA DESA DENGAN PENDEKATAN GOOD GOVERNANCE (STUDI KASUS PADA 19 DESA DI KECAMATAN MERAPI BARAT KABUPATEN LAHAT) - Ghozali, Rosalina; Hari, Kurnia Krisna (Balance : Jurnal Akuntansi dan Bisnis, 2017)
ABSTRACT This study aims to determine the management of village funds with a good governance approach in 19 villages in West Merapi District Lahat District. The formulation of the problem in this study is How Implementation of Village Fund Management done on 19 Villages In West Merapi District Lahat Regency?. Are the principles of good governance applied in managing the Village Funds in 19 villages of West Merapi district of Lahat regency? The research sample consisted of 19 villages of West Merapi sub-district of Lahat Regency. The data used is the result of data processing questionnaire. The results showed that the implementation of village fund management with Good Governance approach based on the analysis of accountability, transparency and participatory variables that the village government has followed the procedures established according to the Minister of Home Affairs Regulation. The village government has also taken into account the costs and benefits, as well as prioritizing the public interest in determining the village fund program in the aim of prospering the people.